1998
DOI: 10.1086/515644
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude, Duration, Quality, and Function of Pneumococcal Vaccine Responses in Elderly Adults

Abstract: The suboptimal efficacy of the currently available 23-valent pneumococcal vaccine in the growing population of adults ú65 years old may be related to the limited immunogenicity of the vaccine polysaccharides in this group. In this study, the majority of elderly outpatients with stable chronic illnesses generated a vigorous IgG response to seven vaccine serotypes comparable to that of healthy young adults at 1, 3, and 16 months after immunization. Moreover, the quality and function of anticapsular antibodies, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
96
2
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(107 citation statements)
references
References 34 publications
7
96
2
2
Order By: Relevance
“…The present study demonstrated that, at 1 month after immunization, the sera of elderly persons had levels of specific capsular antibodies similar to those of healthy younger persons, as reported elsewhere (16,27). For both groups, serotypes 3 and 6B elicited lower increases (<2) and, by this criterion, these antigens appeared to be less immunogenic in both groups (10,26).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The present study demonstrated that, at 1 month after immunization, the sera of elderly persons had levels of specific capsular antibodies similar to those of healthy younger persons, as reported elsewhere (16,27). For both groups, serotypes 3 and 6B elicited lower increases (<2) and, by this criterion, these antigens appeared to be less immunogenic in both groups (10,26).…”
Section: Discussionsupporting
confidence: 88%
“…We also observed that serotypes 1, 5, and 8 induced a high level of humoral response for both groups. As also noted by other investigators (15,16), serotype 8 induced the highest fold increase in the young adult subjects. Actu-ally, the concentration of anti-polysaccharide 8 IgG in 89-SF serum had not been assigned at the time of our study, and therefore we performed the cross-standardization method of Conception and Frasch (31).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These same groups are at greater risk of pneumococcal invasion to the bloodstream and central nervous system, and thus, are at greater risk of death. 8,9 The incidence of pneumococcal infection varies geographically, but increasing rates have been observed in many developed and developing countries. In a survey of 560 pneumococcal blood isolates from patients in Southern Sweden between 1981 and 1996, the incidence of pneumococcal bacteremia increased from 5.2 to 15.2/100 000 per year.…”
Section: Pneumococcal Vaccines Artículo De Revisiónmentioning
confidence: 99%
“…Portanto, pode-se inferir que a idade é um importante fator de risco para colonização pneumocócica e que a sua influência varia de acordo com a fase de crescimento ao longo da vida. De forma semelhante, a distribuição dos sorotipos pneumocócicos também pode variar de acordo com a região geográfica, o tempo e a apresentação clínica dos pacientes, onde a população negra, índios americanos e nativos do Alasca, indivíduos tabagistas, alcoolistas ou com condições médicas crônicas como diabetes, doença falciforme, doenças cardíacas, pulmonares e renais, doenças imunossupressoras, particularmente a AIDS, também fazem parte do grupo de risco (BEREZIN et al, 2007;CARDOZO et al, 2008;DAGAN;LIPSITCH, 2004;RUBINS et al, 1998).…”
Section: Colonização E Fatores De Riscounclassified